Trichogram To Monitor Therapeutic Benefit In Hair Loss - Uppal Monica; Srinivas C R; Kuruvilla K; Thirumurthy M (Wolters Kluwer Medknow Publications, 2004)
Trichogram is a method of quantifying hair. We report 3 cases of diffuse hair loss of varying etiology in whom the improvement after therapeutic intervention could be objectively documented using trichogram.